Analisis Maqashid Asy-Syariah Imam Al-Ghazali Terhadap Hukum Perkawinan Di Indonesia dalam Penyelesaian Sengketa Harta Bersama - Pasaribu, Nurhannah Rosa Delima; Sayehu, Sayehu; Musthafa, Usman; Mukarromah, Oom; Hidayat, Ahmad (Innovative: Journal Of Social Science Research, 2024)
The writing is based on the existence of legal and social gaps in resolving disputes in society. The aim of the writing is to examine efforts to resolve joint property disputes through litigation and non litigation as well as Imam Al-Ghazali's maqashid ash-syariah approach to marriage law in Indonesia regarding joint property. Using a qualitative approach that is descriptive analysis so it includes library research. The literature study concludes that efforts to resolve joint property disputes through litigation and non litigation are a legal process that is resolved through court (litigation) and resolved outside of court (non litigation). Meanwhile, Imam Al-Ghazali's maqashid ash-syariah approach to marriage law in Indonesia regarding joint property is property as a tool (wasilah) which functions to meet life's needs.